Use of CMFDA and CMTMR Fluorescent Dyes in FACS®-Based Antibody Screening - X.-P. Yang; M. Gallo; I. Ngan; M. Nocerini; M.M. Chen (BioTechniques)
Cell-based immunizations are often used when membrane antigens are difficult to purify. To confirm that an antibody binding to the surface of a cell line is, in fact, binding to the desired antigen, FACS® can be performed independently on two cell lines, a transfected cell line expressing the antigen of interest and a control cell line not expressing the antigen. Antibodies binding only to the transfected cell line are then selected for further analysis. This approach can be challenging if a large number of antibodies need to be screened and the antibody quantities are limited. Here we describe a novel method that combines the above two steps of FACS screening into a single step, based on the use of two fluorochromes, CMFDA and CMTMR, to stain transfected and control cell lines, respectively. Antibodies conjugated to a third fluorochrome are then added to the combined cells, followed by three-color FACS analysis. The newly modified FACS method is simple, sensitive, and high throughput. It can be used for antibody screening in multiple cell lines simultaneously.